Novo método para detecção de falhas em estruturas de alumínio utilizando-se impedância elétrica de cerâmicas piezoelétricas e atenuação das ondas ultrassônicas - Costa, Rosalba da (2020)
The aluminum alloy is mainly used in the manufacture of aerial, automotive, prosthetic and orthotic structures, among others. Monitoring and damage detection of these structures is important to ensure the quality of the devices. Thus, many systems based on piezoelectric ceramics have been used to monitor flaws in these structures, however, they operate with high frequency signals. This study proposes a new methodology for nondestructive testing and characterization of these materials using attenuation of ultrasonic waves and electrical impedance of piezoelectric ceramics attached to aluminum alloy bars and plates. Eighteen solid aluminum bars measuring 250 mm × 50 mm × 50 mm were used; in fourteen, three holes of varying diameters and depths were drilled to simulate defects, while four bars were left intact as a reference. Tests were also carried out on five samples of aluminum plates with dimensions of 500 mm × 500 mm × 4 mm, one being a reference and the other four with three holes separated by 125 mm. A 1.6 MHz center frequency transducer, three piezoelectric ceramic plates measuring 12.7 mm × 12.7 mm × 0.52 mm, three ceramic discs of 12.7 mm × 0.267 mm and of 12.7 mm × 1.0 mm were attached to each bar near the manufactured defects and at the same position in the reference sample. To evaluate the aluminum plates, three circular piezoelectric ceramics of 19.05 mm in diameter and 3 mm in thickness were attached to each plate. The electrical impedance was measured with the Agilent 4294A analyzer and the comparison of the signals between the reference samples and those with faults has been done using the RMSD (Root Mean Square Deviation) index. The attenuation of the ultrasonic waves was measured using a Tektronix AFG3021 function generator to excite the ceramic plates attached to the aluminum bars with a single 20 Vpp sine pulse in transmit/receive and pulseecho modes at 90 kHz, 145 kHz, 230 kHz, and 376 kHz. The piezoelectric ceramics attached to the aluminum plates were excited with the same type of pulse at 104 kHz. Broadband attenuation was assessed using two pairs of transducers with center frequency of 500 kHz and 5 MHz, excited with negative pulses of -100 V and duration of 1 μs and 100 ns for 500 kHz and 5 MHz, respectively, using an Olympus 5077PR pulser/receiver. The signals were acquired using a Tektronix TDS2022 digital oscilloscope and then transferred to a computer to be processed in MATLAB®. Finite element simulations were also carried out in ANSYS software. The analysis of the results showed that there was an increase in the RMSD index with the increase in the diameter of the largest flaws (5 mm, 8 mm and 11 mm) and that the same did not occur for samples with smaller flaws (1 mm, 2,5 mm and 3 mm). However, in all cases it was possible to detect the failures with the impedance technique. It was also found that there was a change in the attenuation of the ultrasonic waves that propagated in the damaged samples in relation to those that propagated in the reference ones. Thus, it was possible to conclude that the proposed technique can be used to detect small flaws in aluminum metallic structures, allowing the characterization of these materials using low frequencies.